2019
DOI: 10.17979/cadlaxe.2019.41.0.5823
|View full text |Cite
|
Sign up to set email alerts
|

The granite-related, high-tonnage Sn-Li deposit of Argemela, central Portugal

Abstract: The Argemela Sn-Li quartz vein stockwork, east of the Panasqueira tungsten mine, is hosted in Cambrian slates and greywacke. An underlying Variscan granitic cupola is inferred from spotted slates and albitic microgranite dykes, the last including a thick modified albitic microgranite, enriched in F and Li, exposed some 500 m away, on the hill top. Inferred resources for shallowest deposit portion are 20.1 million tonnes (Mt) at 0.1-0.2% Sn, 0.2% Li and 0.1% (estimate) Rb, but the 650-m vertical-extent of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…29−31 The estimated reserves of the shallowest part of the deposit are 20.1 million tons, and the main lithium minerals are montebrasite and lepidolite. 32 Montebrasite deposits have also been discovered in the Almendra-Souto area and the Alvaros-Goncalo pegmatite vein 33 in Portugal, and Lima and Almeida 34 are conducting detailed investigation. In Tuscany and Rome, Italy, researchers have discovered lithium deposits that can be exploited on a large scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29−31 The estimated reserves of the shallowest part of the deposit are 20.1 million tons, and the main lithium minerals are montebrasite and lepidolite. 32 Montebrasite deposits have also been discovered in the Almendra-Souto area and the Alvaros-Goncalo pegmatite vein 33 in Portugal, and Lima and Almeida 34 are conducting detailed investigation. In Tuscany and Rome, Italy, researchers have discovered lithium deposits that can be exploited on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been found that Yichun, Jiangxi and Songpan, Sichuan also have occurrences of deposits associated with spodumene and montebrasite . The Cambrian shale and limestone in the eastern Argemela area of the Panasqueira tungsten mine in Portugal contain abundant lithium deposits. The estimated reserves of the shallowest part of the deposit are 20.1 million tons, and the main lithium minerals are montebrasite and lepidolite . Montebrasite deposits have also been discovered in the Almendra-Souto area and the Alvaros-Goncalo pegmatite vein in Portugal, and Lima and Almeida are conducting detailed investigation.…”
Section: Introductionmentioning
confidence: 99%